2019
DOI: 10.3389/fpsyg.2019.02278
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Reaction Time, Selective Attention, Physical Activity, and Physical Fitness in Children

Abstract: The objective of this study was to analyze the relationships between simple and complex reaction times (RTs) with the physical activity performed weekly, the physical fitness and selective attention in children of the third cycle of primary education. Participants were 119 children aged between 10 and 12 years (M = 10.71; SD = 0.77). The instruments used for data collection were the D2 attention test to analyze selective attention, various tests of the Eurofit and ALPHA-Fitness Battery to evaluate the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 46 publications
2
59
2
3
Order By: Relevance
“…Specifically, previous studies have indicated the positive effects of physical activity on selective attention in children and adolescents (Janssen et al, 2014;Tine, 2014;Altenburg et al, 2016). Other works have related physical fitness level in children and adolescents with selective attention and concentration, observing that cardiorespiratory aptitude is one of the variables that explains better these associations (Pérez-Lobato et al, 2016;Reloba-Martínez et al, 2017;Reigal et al, 2019a).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, previous studies have indicated the positive effects of physical activity on selective attention in children and adolescents (Janssen et al, 2014;Tine, 2014;Altenburg et al, 2016). Other works have related physical fitness level in children and adolescents with selective attention and concentration, observing that cardiorespiratory aptitude is one of the variables that explains better these associations (Pérez-Lobato et al, 2016;Reloba-Martínez et al, 2017;Reigal et al, 2019a).…”
Section: Introductionmentioning
confidence: 97%
“…In line with previous works [39], as in our research, reaction time has been evaluated by means of an oculo-manual coordination task using the FITLIGHT Trainer system (Sports Corp., Ontario, Canada). In this case the game was mainly based on reactive control including the competition since the two players were performing the game at the same time and they could have the sense of the other's performance.…”
Section: Plos Onementioning
confidence: 80%
“…188 atencional e inhibitorio del funcionamiento cognitivo en estudiantes de EP y ESO. El primer objetivo fue comprobar si existían diferencias entre grupos de escolares que practicaban AFD y un grupo de escolares que no practicaban AFD en el funcionamiento atencional e inhibitorio, en línea con los trabajos previos (González et al, 2018;Moral et al, 2020;Reigal et al, 2019). Los resultados han puesto de manifiesto la existencia de diferencias entre estudiantes que practican AFD y los que no practicaban AFD en los componentes atencionales e inhibitorios.…”
Section: Resultsunclassified
“…Concretamente, los alumnos que practican AFD muestran una menor tasa de errores en tareas de tipo perceptivo, mejores niveles de control (tanto atencional como inhibitorio) y mejor puntuación en los índices de concentración, frente a los estudiantes de la misma edad que no practican AFD. Estos hallazgos están en consonancia con trabajos previos en los que se valora la práctica de actividad física y el funcionamiento ejecutivo, la atención selectiva y la concentración (Guiney, Machado, 2013;Pérez et al, 2016;Reigal et al, 2016, Reigal et al, 2019. Sin embargo, no se han encontrado diferencias ni en la velocidad de procesamiento, ni en la cantidad de trabajo realizado entre los grupos estudiados.…”
Section: Resultsunclassified